Future climate and its potential impact on the spatial and temporal hydrological regime in the Koshi Basin, Nepal - Sagar Ratna Bajracharya; Saurav Pradhananga; Arun Bhakta Shrestha; Rajesh Thapa (Journal of Hydrology: Regional Studies, 2023)
Study region: Koshi River basin, Eastern Nepal. Study focus: Climate change is increasingly evident as the global surface temperature is warming with erratic rainfall patterns across the globe. In this regard, the Koshi Basin in the Himalayan region is also impacted, and it is important to understand the spatio-temporal details of the impact in the basin under future climate change. This study assessed the potential climate change and its impact on the hydrological regime using the Soil and Water Assessment Tool (SWAT) and Indicators of Hydrological Alteration (IHA) based on RCP4.5 and RCP8.5 of ensemble downscaled CMIP5 GCM runs. New hydrological insights for this region: Results show the upper part of the basin warming faster than the lower part, the pre-monsoon season warming more than other seasons. There is no clear uniform trend in precipitation. However, the southeastern part of the basin will get more precipitation. Sub-basins will get more precipitation during the post-monsoon under RCP4.5, and during the monsoon under RCP8.5. The annual water availability will not decline but water availability within seasons and regions is projected to be highly variable. There is also a change in the spatial pattern of river discharge and the western part of the basin is likely to experience more impact. Therefore, these findings will be valuable in identifying how particular sub-basins within the Koshi Basin will be impacted by climate change and in stipulating effective planning and management of water resources for the future.